Catalytic Decomposition Of Short Chain Alcohol In Air On Bimetallic Ion-exchanged H-BEA Zeolites. - Abdullah, Ahmad Zuhairi; Bakar, M Zailani Abu; Bhatia, Subhash (2001)
The catalytic decomposition of methanol (MeOH) over different bimetallic exchange combinations of Co, Cr and Cu and zeotite Beta (HBEA) was studied using a fixed-bed catalytic reactor in the tcmperature range of l50-450C, at partial pressure oI 1.2% and GHSV of 26,500 hour1.